Two-component developer
Patent Information
- Application Number
- JP2023533434
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-09
- Filing Date
- 2022-03-31
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-03-31
AI Technical Summary
【0007】 本発明に係る二成分現像剤によれば、かぶりの少ない画像を形成でき、トナー濃度が変化した場合でもトナーの帯電量の変動が小さくなる。
Smart Images

Figure 0007639919000007 
Figure 0007639919000001 
Figure 0007639919000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a two-component developer. [Background technology]
[0002] An image forming apparatus that uses a toner to form an image is required to stably charge the toner to a desired range of charge amount. Titanate compounds have a relatively high relative dielectric constant, so that the charge amount of the toner tends to be able to be maintained within a desired range even after a large number of sheets are printed. For this reason, toners containing titanate compound particles as external additive particles have been considered. For example, the toner described in Patent Document 1 contains toner particles, and the toner particles include titanate compound particles doped with lanthanum and a group 5 element of the periodic table as external additive particles. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-181051 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the toner described in Patent Document 1 has room for improvement in terms of forming an image with less fog and reducing the fluctuation in the charge amount of the toner when the toner concentration in a two-component developer changes.
[0005] The present invention has been made in consideration of the above problems, and its object is to provide a two-component developer that can form images with less fog and has small fluctuations in the amount of charge of the toner even when the toner concentration changes. [Means for solving the problem]
[0006] The two-component developer according to the present invention includes a toner containing toner particles and a carrier containing carrier particles. The toner particles include toner base particles and external additive particles provided on the surfaces of the toner base particles. The external additive particles include strontium titanate particles. A first content rate, which is a content rate of the strontium titanate particles relative to the mass of the toner base particles, is 0.30 mass% or more and 0.90 mass% or less. The carrier particles include a carrier core and a coating layer that covers the surface of the carrier core. The coating layer contains a coating resin and barium titanate particles. The coating resin contains a silicone resin. The number-average primary particle diameter of the barium titanate particles is 100 nm or more and 500 nm or less. A second content rate, which is a content rate of the coating layer relative to the mass of the carrier core, is 2.0 mass% or more and 4.0 mass% or less. A third content rate, which is a content rate of the barium titanate relative to the mass of the coating resin, satisfies formula (1). In the formula (1), X represents the first content, and Z represents the third content. (X × 10) ≦ Z ≦ 45.0 (1) Effect of the Invention
[0007] According to the two-component developer of the present invention, an image with little fog can be formed, and the fluctuation in the charge amount of the toner is small even when the toner concentration changes. [Brief description of the drawings]
[0008] [Figure 1] 1 is a diagram showing a two-component developer according to an embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] First, the meaning of the terms used in this specification and the measurement method will be explained. A toner is an aggregate (for example, powder) of toner particles. An external additive is an aggregate (for example, powder) of external additive particles. A carrier is an aggregate (for example, powder) of carrier particles. Unless otherwise specified, the evaluation results (values indicating shape, physical properties, etc.) of a powder (more specifically, a powder of toner particles, a powder of external additive particles, a powder of carrier particles, etc.) are the number average of values measured for each of the particles selected from a considerable number of particles from the powder. Unless otherwise specified, the "main component" of a material means the component that is contained most in the material on a mass basis. The strength of hydrophobicity (or strength of hydrophilicity) can be expressed, for example, by the contact angle of a water droplet (ease of wetting with water). The larger the contact angle of the water droplet, the stronger the hydrophobicity. The compound and its derivatives may be collectively referred to by adding "system" after the name of the compound. When the name of a polymer is expressed by adding "based" after the name of a compound, it means that the repeating unit of the polymer is derived from the compound or a derivative thereof. Each component described in this specification may be used alone or in combination of two or more kinds.
[0010] Volume median diameter of powder (D 50) is the median diameter measured using a laser diffraction / scattering particle size distribution analyzer (HORIBA, Ltd., "LA-950"). The number-average primary particle diameter of a powder is the number average of the circle-equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) measured using a scanning electron microscope, unless otherwise specified. The number-average primary particle diameter of a powder is, for example, the number average of the circle-equivalent diameters of 100 primary particles. The softening point (Tm) is a value measured using a high-temperature flow tester (Shimadzu Corporation, "CFT-500D"), unless otherwise specified. In the S-shaped curve (horizontal axis: temperature, vertical axis: stroke) measured using the high-temperature flow tester, the temperature at which "(baseline stroke value + maximum stroke value) / 2" corresponds to the softening point. The measured value of the melting point (Mp), unless otherwise specified, is the temperature of the maximum endothermic peak in the endothermic curve (vertical axis: heat flow (DSC signal), horizontal axis: temperature) measured using a differential scanning calorimeter (Seiko Instruments Inc.'s "DSC-6220"). This endothermic peak appears due to melting of the crystallized portion. The measured value of the glass transition point (Tg), unless otherwise specified, is the value measured according to "JIS (Japanese Industrial Standards) K7121-2012" using a differential scanning calorimeter (Seiko Instruments Inc.'s "DSC-6220"). In the endothermic curve (vertical axis: heat flow (DSC signal), horizontal axis: temperature) measured using a differential scanning calorimeter, the temperature of the inflection point due to glass transition (specifically, the temperature of the intersection between the extrapolated line of the baseline and the extrapolated line of the falling line) corresponds to the glass transition point. Unless otherwise specified, each measured value of the acid value and hydroxyl value is a value measured according to "JIS (Japanese Industrial Standards) K0070-1992". Unless otherwise specified, each measured value of the mass average molecular weight (Mw) is a value measured using gel permeation chromatography. Unless otherwise specified, the strength of electrostatic chargeability is the ease of triboelectric charging with respect to a standard carrier provided by the Imaging Society of Japan. For example, the measurement object is triboelectrically charged by stirring the measurement object with a standard carrier (anionic: N-01, cationic: P-01) provided by the Imaging Society of Japan.For example, a Q / m meter (Trek's "MODEL 212HS") is used to measure the surface potential of the object before and after frictional charging, and the larger the change in potential before and after frictional charging is, the stronger the chargeability of the object. The meanings of the terms used in this specification and the measurement method have been explained above.
[0011] [Two-component developer] A two-component developer (hereinafter, sometimes referred to as developer) 1 according to an embodiment of the present invention will be described below with reference to Fig. 1. Fig. 1 shows developer 1 according to this embodiment. In Fig. 1, multiple identical elements are indicated by the same hatching, one of these identical elements is given a reference number, and the remaining reference numbers of these identical elements are omitted.
[0012] The developer 1 includes a toner and a carrier. The toner includes toner particles 10. The carrier includes carrier particles 20. The toner particles 10 include toner base particles 11 and external additive particles 12. The external additive particles 12 are provided on the surfaces of the toner base particles 11. The external additive particles 12 include strontium titanate particles 13. A first content rate, which is a content rate of the strontium titanate particles 13 relative to the mass of the toner base particles 11, is 0.30 mass% or more and 0.90 mass% or less. The carrier particles 20 include a carrier core 21 and a coating layer 22. The coating layer 22 covers the surface of the carrier core 21. The coating layer 22 includes a coating resin and barium titanate particles 23. The coating resin includes a silicone resin. The number average primary particle diameter of the barium titanate particles 23 is 100 nm or more and 500 nm or less. A second content, which is the content of the coating layer 22 relative to the mass of the carrier core 21, is 2.0 mass% or more and 4.0 mass% or less. A third content, which is the content of the barium titanate particles 23 relative to the mass of the coating resin, satisfies formula (1). In formula (1), X represents the first content, and Z represents the third content. (X × 10) ≦ Z ≦ 45.0 (1)
[0013] Hereinafter, the "first content, which is the content of strontium titanate particles 13 relative to the mass of toner base particles 11" may be referred to as "ST / base particle ratio." Also, the "second content, which is the content of coating layer 22 relative to the mass of carrier core 21" may be referred to as "coating layer / core ratio." Also, the "third content, which is the content of barium titanate particles 23 relative to the mass of coating resin" may be referred to as "BT / coating resin ratio." All of the first content, second content, and third content are percentages (unit: mass%).
[0014] With the above-described configuration, the developer 1 according to the present embodiment can form an image with less fog, and the fluctuation in the charge amount of the toner is small even when the toner concentration in the developer 1 changes. The reason for this is presumed to be as follows.
[0015] In the developer 1 according to this embodiment, the toner particles 10 contain strontium titanate particles 13 as external additive particles 12. Since the relative dielectric constant of the strontium titanate particles 13 is relatively high, the electrostatic capacitance of the toner particles 10 containing the strontium titanate particles 13 is relatively large. The larger the electrostatic capacitance, the greater the amount of triboelectric charge of the toner particles 10, and therefore the toner particles 10 are more likely to be charged to a desired range of charge amount. As a result, the number of toner particles 10 whose charge amount is less than the desired value and the number of toner particles 10 that are oppositely charged are reduced, and an image with less fog can be formed.
[0016] However, the larger the electrostatic capacitance of the toner particles 10, the greater the charge acceptance of the toner particles 10. For this reason, if the ability of the carrier particles 20 to charge the toner particles 10 due to friction (hereinafter, sometimes referred to as charge imparting ability) is low, it becomes difficult for the carrier particles 20 to supply an amount of charge corresponding to the charge acceptance to the toner particles 10. As a result, when the toner concentration in the developer changes, the charge amount of the toner changes significantly.
[0017] Therefore, in the developer 1 according to this embodiment, the coating layer 22 of the carrier particle 20 contains barium titanate particles 23. Since the relative dielectric constant of the barium titanate particles 23 is relatively high, the electrostatic capacity of the carrier particle 20 containing the barium titanate particles 23 in the coating layer 22 is relatively large. The larger the electrostatic capacity, the larger the triboelectric charge amount (the triboelectric charge amount of the opposite polarity to that of the toner particle 10) of the carrier particle 20, and therefore the charge imparting ability of the carrier particle 20 becomes high. As a result, an amount of charge corresponding to the charge acceptance amount of the toner particle 10 is supplied from the carrier particle 20 to the toner particle 10. This makes it possible to reduce the fluctuation in the charge amount of the toner even when the toner concentration in the developer 1 changes.
[0018] In the developer 1 according to the present embodiment, the ST / base particle ratio of the toner particles 10 is 0.30% by mass or more and 0.90% by mass or less. When the ST / base particle ratio is 0.30% by mass or more, the electrostatic capacity of the toner particles 10, and therefore the triboelectric charge amount, becomes sufficiently large. Therefore, the toner particles 10 can be charged to a desired range of charge amount, and an image with less fog can be formed. On the other hand, when the ST / base particle ratio is 0.90 mass or less, the strontium titanate particles 13 are less likely to be detached from the toner base particles 11. Therefore, the detached strontium titanate particles 13 are less likely to hinder the contact between the toner particles 10 and the carrier particles 20. As a result, the toner particles 10 can be charged to a desired range of charge amount by friction, and an image with less fog can be formed.
[0019] In the developer 1 according to the present embodiment, the number average primary particle diameter of the barium titanate particles 23 is 100 nm or more and 500 nm or less. If the number average primary particle diameter of the barium titanate particles 23 is less than 100 nm, the relative dielectric constant tends to decrease. If the number average primary particle diameter of the barium titanate particles 23 is 100 nm or more, the relative dielectric constant of the barium titanate particles 23 becomes sufficiently high, and the electrostatic capacity of the carrier particles 20 becomes large. As a result, even if the toner concentration in the developer 1 changes, the variation in the charge amount of the toner can be reduced. On the other hand, if the number average primary particle diameter of the barium titanate particles 23 is 500 nm or less, the barium titanate particles 23 are taken into the coat layer 22 and are difficult to detach from the coat layer 22. Therefore, the detached barium titanate particles 23 are unlikely to hinder the contact between the toner particles 10 and the carrier particles 20. As a result, the toner particles 10 can be charged to a desired range of charge amount by friction, and an image with little fog can be formed.
[0020] In the developer 1 according to the present embodiment, the coat layer / core ratio of the carrier particles 20 is 2.0% by mass or more and 4.0% by mass or less. When the coat layer / core ratio is 2.0% by mass or more, the carrier cores 21 are sufficiently covered with the coat layer 22. As a result, the toner particles 10 can be charged to a desired range of charge amount by friction between the coat layer 22 of the carrier particles 20 and the toner particles 10, and an image with less fog can be formed. On the other hand, when the coat layer / core ratio exceeds 4.0% by mass, the coat layer 22 becomes thick and the electrostatic capacity of the carrier particles 20 is likely to decrease. When the coat layer / core ratio is 4.0% by mass or less, the electrostatic capacity of the carrier particles 20 becomes large, and even when the toner concentration in the developer 1 changes, the fluctuation in the charge amount of the toner can be reduced. In addition, when the coat layer / core ratio is 4.0% by mass or less, the carrier particles 20 can be suppressed from coagulating with each other when the coat layer 22 is formed in the carrier formation process described later. Since the toner particles 10 are suitably charged by friction with the non-aggregated or less-aggregated carrier particles 20, the toner particles 10 can be charged to a desired charge amount, and an image with less fog can be formed.
[0021] In the developer 1 according to the present embodiment, the BT / coat resin ratio of the carrier particles 20 satisfies the formula (1) "(X×10)≦Z≦45.0". That is, Z (unit: mass %) is X×10 mass % or more and 45.0 mass % or less. When Z in the formula (1) (i.e., the BT / coat resin ratio of the carrier particles 20) is X×10 (i.e., the value obtained by multiplying the ST / base particle ratio of the toner particles 10 by 10) or more, the electrostatic capacity of the carrier particles 20 becomes sufficiently large with respect to the electrostatic capacity of the toner particles 10. As a result, an amount of charge corresponding to the charge acceptance amount of the toner particles 10 is supplied from the carrier particles 20 to the toner particles 10. This makes it possible to reduce the fluctuation in the charge amount of the toner even if the toner concentration in the developer 1 changes. On the other hand, when Z in formula (1) (i.e., BT / coat resin ratio of carrier particles 20) exceeds 45.0, the amount of barium titanate particles 23 becomes too large, and some of the barium titanate particles 23 tend to be detached from the coat layer 22 without being incorporated therein. When Z is 45.0 or less, the barium titanate particles 23 are incorporated into the coat layer 22, and are less likely to be detached from the coat layer 22. Therefore, the barium titanate particles 23 detached from the coat layer 22 are less likely to hinder contact between the toner particles 10 and the carrier particles 20, and the toner particles 10 can be charged to a desired range of charge amount by friction. As a result, an image with less fog can be formed.
[0022] The reasons why the developer 1 according to this embodiment can form an image with little fog and the fluctuation in the charge amount of the toner is small even when the toner concentration in the developer 1 changes have been explained above.
[0023] As already mentioned, when the ST / base particle ratio is 0.90 by mass or less, the strontium titanate particles 13 are difficult to detach from the toner base particles 11. Also, as already mentioned, when Z in formula (1) is 45.0 or less, the barium titanate particles 23 are taken into the coating layer 22 and are difficult to detach from the coating layer 22. For these reasons, the developer 1 according to this embodiment can prevent the strontium titanate particles 13 or the barium titanate particles 23 from being detached and carried to the gap between the cleaning blade and the photosensitive drum. As a result, the load on the cleaning blade can be reduced. Next, the toner and carrier contained in the developer 1 will be described in more detail.
[0024] [toner] The toner includes toner particles 10. The toner particles 10 include toner base particles 11 and external additive particles 12. The external additive particles 12 are provided on the surfaces of the toner base particles 11. The external additive particles 12 and the toner base particles 11 will be described below.
[0025] <External additive particles> The external additive particles 12 include strontium titanate particles 13. The external additive particles 12 may further include external additive particles (hereinafter, sometimes referred to as other external additive particles) 14 other than the strontium titanate particles 13, as necessary. However, the other external additive particles 14 can be omitted. The strontium titanate particles 13 and the other external additive particles 14 will be described below.
[0026] (Strontium titanate particles) As already described, the ST / base particle ratio is 0.30% by mass or more and 0.90% by mass or less. In order to form an image with little fog, the ST / base particle ratio is preferably 0.35 to 0.80, and more preferably 0.40 to 0.70.
[0027] In order to form an image with less fog and to reduce fluctuations in the charge amount of the toner when the toner concentration in the developer 1 changes, the number average primary particle diameter of the strontium titanate particles 13 is preferably 20 nm or more and 80 nm or less, more preferably 30 nm or more and 80 nm or less, even more preferably 50 nm or more and 80 nm or less, and even more preferably 60 nm or more and 80 nm or less.
[0028] The strontium titanate particles 13 may be doped or undoped. Since the capacitance of the toner particles 10 can be made sufficiently large to form an image with little fog, the strontium titanate particles 13 may be undoped strontium titanate particles. For example, the strontium titanate particles 13 may be strontium titanate particles that are not doped with lanthanum and an element of Group 5 of the periodic table (e.g., niobium, tantalum).
[0029] (Other external additive particles) Examples of the other external additive particles 14 include silica particles, alumina particles, magnesium oxide particles, and zinc oxide particles. The other external additive particles 14 may be surface-treated. For example, when silica particles are used as the other external additive particles 14, the surface of the silica particles may be given hydrophobicity and / or positive chargeability by a surface treatment agent. The number-average primary particle diameter of the other external additive particles 14 is preferably 1 nm or more and 60 nm or less, and more preferably 5 nm or more and 25 nm or less. The amount of the other external additive particles 14 is preferably 0.1 parts by mass or more and 10.0 parts by mass or less, and more preferably 1.0 parts by mass or more and 2.0 parts by mass or less, relative to 100.0 parts by mass of the toner mother particles 11.
[0030] <Toner base particles> The toner base particles 11 contain at least one selected from the group consisting of, for example, a binder resin, a colorant, a charge control agent, and a release agent. The binder resin, the colorant, the charge control agent, and the release agent will be described below.
[0031] (Binding resin) In order to obtain a toner having excellent low-temperature fixing properties, the toner base particles 11 preferably contain a thermoplastic resin as a binder resin, and more preferably contain a thermoplastic resin at a ratio of 85% by mass or more of the total binder resin. Examples of the thermoplastic resin include polyester resin, styrene resin, acrylic acid ester resin (more specifically, acrylic acid ester polymer, methacrylic acid ester polymer, etc.), olefin resin (more specifically, polyethylene resin, polypropylene resin, etc.), vinyl resin (more specifically, vinyl chloride resin, polyvinyl alcohol, vinyl ether resin, N-vinyl resin, etc.), polyamide resin, and urethane resin. Copolymers of these resins, that is, copolymers in which any repeating unit is introduced into the above resin (more specifically, styrene-acrylic resin, styrene-butadiene resin, etc.) can also be used as the binder resin.
[0032] The binder resin is preferably a polyester resin. The polyester resin is a polymer of one or more polyhydric alcohol monomers and one or more polycarboxylic acid monomers. Instead of the polycarboxylic acid monomer, a polycarboxylic acid derivative (more specifically, a polycarboxylic acid anhydride, a polycarboxylic acid halide, etc.) may be used.
[0033] Examples of polyhydric alcohol monomers include diol monomers, bisphenol monomers, and trihydric or higher alcohol monomers.
[0034] Examples of diol monomers include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 2-butene-1,4-diol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 1,4-benzenediol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0035] Examples of bisphenol monomers include bisphenol A, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A, and propylene oxide adducts of bisphenol A.
[0036] Examples of trihydric or higher alcohol monomers include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, diglycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0037] Examples of polycarboxylic acid monomers include dicarboxylic acid monomers and tricarboxylic or higher carboxylic acid monomers.
[0038] Examples of divalent carboxylic acid monomers include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, 5-sulfoisophthalic acid, 5-sodium sulfoisophthalate, cyclohexanedicarboxylic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, succinic acid, alkyl succinic acid, and alkenyl succinic acid. Examples of alkyl succinic acid include n-butyl succinic acid, isobutyl succinic acid, n-octyl succinic acid, n-dodecyl succinic acid, and isododecyl succinic acid. Examples of alkenyl succinic acid include n-butenyl succinic acid, isobutenyl succinic acid, n-octenyl succinic acid, n-dodecenyl succinic acid, and isododecenyl succinic acid.
[0039] Examples of trivalent or higher carboxylic acid monomers include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, and empol trimer acid.
[0040] The polyester resin is preferably a polymer of a bisphenol monomer, a divalent carboxylic acid monomer, and a trivalent carboxylic acid monomer. The polyester resin is more preferably a polymer of a bisphenol A alkylene oxide adduct, a dicarboxylic acid having 3 to 6 carbon atoms, and an aryl tricarboxylic acid. The polyester resin is further preferably a polymer of a bisphenol A ethylene oxide adduct, a bisphenol A propylene oxide adduct, fumaric acid, and trimellitic acid.
[0041] The polyester resin is preferably a non-crystalline polyester resin. For non-crystalline polyester resins, it is often impossible to measure a clear melting point. Therefore, a polyester resin that does not show a clear endothermic peak in an endothermic curve measured using a differential scanning calorimeter may be judged to be a non-crystalline polyester resin.
[0042] The softening point of the polyester resin is preferably from 50° C. to 200° C., and more preferably from 80° C. to 120° C. The glass transition point of the polyester resin is preferably from 40° C. to 100° C., and more preferably from 40° C. to 60° C.
[0043] The mass average molecular weight of the polyester resin is preferably 10,000 or more and 50,000 or less, and more preferably 20,000 or more and 40,000 or less.
[0044] The acid value of the polyester resin is preferably from 1 mgKOH / g to 30 mgKOH / g, more preferably from 10 mgKOH / g to 20 mgKOH / g, and the hydroxyl value of the polyester resin is preferably from 1 mgKOH / g to 50 mgKOH / g, more preferably from 20 mgKOH / g to 40 mgKOH / g.
[0045] (Coloring agent) As the colorant, a known pigment or dye can be used in accordance with the color of the toner, and examples of the colorant include a black colorant, a yellow colorant, a magenta colorant, and a cyan colorant.
[0046] An example of the black colorant is carbon black. The black colorant may be a colorant that is toned black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0047] As the yellow colorant, for example, one or more compounds selected from the group consisting of condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and arylamide compounds can be used. As the yellow colorant, for example, CI Pigment Yellow (3, 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 191, and 194), Naphthol Yellow S, Hansa Yellow G, and CI Vat Yellow can be mentioned.
[0048] As the magenta colorant, for example, one or more compounds selected from the group consisting of condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds can be used. As the magenta colorant, for example, CI Pigment Red (2, 3, 5, 6, 7, 19, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254) can be used.
[0049] As the cyan colorant, for example, one or more compounds selected from the group consisting of copper phthalocyanine compounds, anthraquinone compounds, and basic dye lake compounds can be used. As the cyan colorant, for example, CI Pigment Blue (1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66), phthalocyanine blue, CI Vat Blue, and CI Acid Blue can be mentioned.
[0050] The amount of the colorant is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0051] (Charge control agent) The charge control agent is used, for example, for the purpose of obtaining a toner having excellent charge stability and charge rise characteristics. The charge rise characteristics of the toner are an index of whether the toner can be charged to a predetermined charge level in a short time. Examples of the charge control agent include a positive charge control agent and a negative charge control agent. The cationic property (positive chargeability) of the toner can be strengthened by adding a positive charge control agent to the toner base particles 11, and the anionic property (negative chargeability) of the toner can be strengthened by adding a negative charge control agent to the toner base particles 11. Examples of the positive charge control agent include pyridine, nigrosine, and quaternary ammonium salts. Examples of the negative charge control agent include metal-containing azo dyes, sulfo group-containing resins, oil-soluble dyes, naphthenic acid metal salts, acetylacetone metal complexes, salicylic acid metal complexes, boron compounds, fatty acid soaps, and long-chain alkyl carboxylates. However, if sufficient chargeability is ensured in the toner, it is not necessary to add a charge control agent to the toner base particles 11. The amount of the charge control agent is preferably 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0052] (Release agent) The release agent is used, for example, for the purpose of obtaining a toner having excellent hot offset resistance. Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, plant-derived waxes, animal-derived waxes, mineral-derived waxes, ester waxes mainly composed of fatty acid esters, and waxes in which fatty acid esters are partially or completely deoxidized. Examples of the aliphatic hydrocarbon waxes include polyethylene waxes (e.g., low molecular weight polyethylene), polypropylene waxes (e.g., low molecular weight polypropylene), polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the plant-derived waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal-derived waxes include beeswax, lanolin, and spermaceti. Examples of the mineral-derived waxes include ozokerite, ceresin, and petrolatum. Examples of ester waxes that are mainly composed of fatty acid ester include Montan acid ester wax and castor wax. Examples of waxes in which the fatty acid ester is partially or completely deoxidized include deoxidized carnauba wax. The amount of the release agent is preferably 1 part by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0053] The toner particles 10 may contain known additives as necessary. The volume median diameter of the toner particles 10 is preferably 4 μm or more and 12 μm or less. The volume median diameter of the toner base particles 11 is preferably 4 μm or more and 12 μm or less, more preferably 5 μm or more and 9 μm or less. The toner particles 10 may be magnetic toner or non-magnetic toner. When the toner particles 10 are magnetic toner, the toner base particles 11 further contain magnetic powder. In the developer 1, the amount of the toner is preferably 1 part by mass or more and 15 parts by mass or less, more preferably 3 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the carrier. For ease of explanation, FIG. 1 shows a non-capsule toner base particle 11. However, the toner base particle 11 shown in FIG. 1 may be a capsule toner base particle having a shell layer covering the toner core, with the toner base particle 11 being a toner core. The toner has been described above.
[0054] [Career] The carrier includes carrier particles 20. The carrier particles 20 have a carrier core 21 and a coating layer 22. The coating layer 22 is provided on the surface of the carrier core 21. The coating layer 22 coats the surface of the carrier core 21. The coating layer 22 may coat the entire surface of the carrier core 21, or may coat only a portion of the surface of the carrier core 21.
[0055] As already mentioned, the coat layer / core ratio is 2.0% by mass or more and 4.0% by mass or less. In order to form an image with less fog, the coat layer / core ratio is preferably 2.1% by mass or more, and more preferably 2.2% by mass or more. In order to reduce the fluctuation in the charge amount of the toner when the toner concentration in the developer 1 changes, the coat layer / core ratio is preferably 3.9% by mass or less, and more preferably 3.0% by mass or less. Hereinafter, the carrier core 21 and the coat layer 22 of the carrier particle 20 will be described.
[0056] <Career Core> The carrier core 21 contains, for example, a magnetic material. Examples of the magnetic material contained in the carrier core 21 include metal oxides, more specifically, magnetite, maghemite, and ferrite. Ferrite has a tendency to have high fluidity and to be chemically stable. For this reason, from the viewpoint of forming high-quality images over a long period of time, it is preferable that the carrier core 21 contains ferrite. Examples of ferrite include barium ferrite, manganese ferrite (Mn-ferrite), Mn-Zn ferrite, Ni-Zn ferrite, Mn-Mg ferrite, Ca-Mg ferrite, Li ferrite, and Cu-Zn ferrite. The shape of the carrier core 21 is not particularly limited, and may be an irregular shape or a spherical shape. As the carrier core 21, a commercially available product may be used. In addition, the carrier core 21 may be produced by crushing and firing a magnetic material.
[0057] The volume median diameter of the carrier core 21 is preferably 20.0 μm or more and 60.0 μm or less, more preferably 20.0 μm or more and less than 40.0 μm, and particularly preferably 20.0 μm or more and 35.0 μm or less. When the volume median diameter of the carrier core 21 is 20.0 μm or more, the carrier particles 20 are less likely to adhere to the photosensitive drum (carrier development). This makes it possible to prevent the carrier particles 20 adhered to the photosensitive drum from moving from the photosensitive drum to the transfer section, thereby preventing image defects such as transfer defects. In addition, since carrier development is less likely to occur, the occurrence of cleaning defects can be prevented. On the other hand, when the volume median diameter of the carrier core 21 is 60.0 μm or less, the magnetic brush of the developer 1 formed on the peripheral surface of the developing roller during image formation becomes fine, and an image of high image quality can be formed.
[0058] The saturation magnetization of the carrier core 21 is preferably 65 emu / g or more and 90 emu / g or less. When the carrier core 21 contains Mn-ferrite, the higher the Mn content, the lower the saturation magnetization of the carrier core 21 tends to be. When the carrier core 21 contains Mn-Mg ferrite, the higher the Mg content, the lower the saturation magnetization of the carrier core 21 tends to be.
[0059] <Coat layer> The coating layer 22 contains a coating resin and barium titanate particles 23. The coating layer 22 preferably further contains carbon black particles 24. However, the coating layer 22 does not necessarily contain carbon black particles 24. The coating resin, the barium titanate particles 23, and the carbon black particles 24 will be described below.
[0060] (coating resin) In order to effectively triboelectrically charge the toner, the coating resin contains a silicone resin. Suitable examples of silicone resins include silicone resins having a methyl group and epoxy resin-modified silicone resins. An example of a silicone resin having a methyl group is a silicone resin having a methyl group and no phenyl group. Another example of a silicone resin having a methyl group is a silicone resin having a methyl group and a phenyl group (hereinafter sometimes referred to as "methylphenyl silicone resin"). The coating layer 22 may contain only a silicone resin as a coating resin, or may further contain a resin other than a silicone resin.
[0061] (Barium titanate particles) As already mentioned, the number average primary particle diameter of the barium titanate particles 23 is 100 nm or more and 500 nm or less. In order to reduce the fluctuation in the charge amount of the toner when the toner concentration in the developer 1 changes, the number average primary particle diameter of the barium titanate particles 23 is preferably 200 nm or more. In order to form an image with less fog, the number average primary particle diameter of the barium titanate particles 23 is preferably 400 nm or less.
[0062] As already mentioned, the BT / coating resin ratio satisfies the formula (1) "(X×10)≦Z≦45.0". In the formula (1), Z represents the BT / coating resin ratio, but when the coating resin is two or more types of resin, the mass of the coating resin means the total mass of the two or more types of resin. In order to reduce the fluctuation in the charge amount of the toner when the toner concentration in the developer 1 changes, Z in formula (1) is preferably 11 times X (i.e., X×11) or more, more preferably 12 times X (i.e., X×12) or more, even more preferably 15 times X (i.e., X×15) or more, even more preferably 20 times X (i.e., X×20) or more, even more preferably 30 times X (i.e., X×30) or more, even more preferably 50 times X (i.e., X×50) or more, even more preferably 80 times X (i.e., X×80) or more, and particularly preferably 100 times X (i.e., X×100) or more. On the other hand, in order to form an image with less fog, Z in formula (1) is preferably 44.0 or less, more preferably 43.0 or less, even more preferably 42.0 or less, still more preferably 40.0 or less, even more preferably 30.0 or less, still more preferably 20.0 or less, and particularly preferably 15.0 or less.
[0063] The method for producing the barium titanate particles 23 is not particularly limited, but may be, for example, a hydrothermal synthesis method. The true specific gravity of the barium titanate particles 23 produced by the hydrothermal synthesis method is small because of the voids inside. In addition, the particle size distribution of the barium titanate particles 23 produced by the hydrothermal synthesis method is sharp. For these reasons, the barium titanate particles 23 produced by the hydrothermal synthesis method are easily uniformly dispersed in the coating resin, and a carrier having a uniform charge imparting ability is easily obtained. For this reason, the barium titanate particles 23 are preferably a hydrothermal synthesis product.
[0064] The hydrothermal synthesis method includes, for example, a hydrothermal reaction step and a heat treatment step. In the hydrothermal reaction step, a water-soluble barium salt is added to a titanium oxide dispersion liquid in which titanium oxide particles are dispersed, and the mixture is heated to cause a hydrothermal reaction. In this way, barium titanate hydrothermally synthesized particles are obtained. In the heat treatment step, the barium titanate hydrothermally synthesized particles are heat-treated to obtain barium titanate particles 23. The heating temperature in the hydrothermal reaction step is preferably 80°C or higher. The heat treatment temperature in the heat treatment step is preferably 650°C or higher and 850°C or lower. The number-average primary particle diameter of the barium titanate particles 23 can be adjusted, for example, by changing the heating temperature in the hydrothermal reaction step and the time for hydrothermal reaction. For example, the higher the heating temperature in the hydrothermal reaction step, the larger the number-average primary particle diameter of the barium titanate particles 23. In addition, the longer the time for hydrothermal reaction, the larger the number-average primary particle diameter of the barium titanate particles 23.
[0065] (Carbon black particles) Since the carbon black particles 24 are conductive, the inclusion of the carbon black particles 24 in the coating layer 22 allows the charge to move smoothly from the carrier particles 20 to the toner particles 10. As a result, the toner particles 10 can be charged to a desired charge amount, and an image with less fog can be formed. The number-average primary particle diameter of the carbon black particles 24 is preferably 10 nm or more and 50 nm or less, and more preferably 30 nm or more and 40 nm or less. The DBP oil absorption of the carbon black particles 24 is 300 cm 3 / 100g or more 700cm 3 / 100g or less is preferable, and 400cm 3 / 100g or more 600cm 3 The BET specific surface area of the carbon black particles 24 is preferably 1000 m / 100 g or less. 2 / g or more 2000m 2 / g or less, and 2 / g or more 1500m 2The amount of the carbon black particles 24 is preferably 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the coating resin.
[0066] The carrier particles 20 may contain known additives as necessary. The volume median diameter of the carrier particles 20 is preferably 25 μm or more and 100 μm or less. The carrier has been described above.
[0067] [Developer manufacturing method] An example of a method for producing the developer 1 according to the present embodiment will be described below. The method for producing the developer 1 according to the present embodiment includes, for example, a toner forming step, a carrier forming step, and a mixing step of the toner and the carrier.
[0068] <Toner formation process> In the toner forming process, for example, a binder resin, a colorant, a charge control agent, and a release agent are mixed to obtain a mixture. The mixture is melted and kneaded to obtain a melted and kneaded product. The melted and kneaded product is pulverized to obtain a pulverized product. The pulverized product is classified to obtain toner base particles 11. The toner base particles 11 and external additive particles 12 (strontium titanate particles 13 and any other external additive particles 14) are mixed using a mixer. By mixing, the external additive particles 12 are attached to the surfaces of the toner base particles 11, and a toner containing toner particles 10 is obtained. Mixing with the external additive particles 12 is preferably performed under conditions in which the external additive particles 12 are not completely embedded in the toner base particles 11. The external additive particles 12 are attached to the surfaces of the toner base particles 11 by physical bonds (physical forces) rather than chemical bonds.
[0069] <Carrier formation process> In the carrier formation process, a coating layer 22 is formed on the surface of the carrier core 21 to obtain a carrier containing carrier particles 20. For example, a coating liquid containing a coating resin, barium titanate particles 23, and optional carbon black particles 24 is sprayed onto the carrier core 21 in the fluidized bed. Next, the carrier core 21 onto which the coating liquid has been sprayed is heated at a first predetermined temperature (hereinafter, may be referred to as a predetermined drying temperature) to dry the coating liquid attached to the surface of the carrier core 21 to obtain a dried product. Next, the dried product is heated at a second predetermined temperature (hereinafter, may be referred to as a predetermined baking temperature) using an electric furnace to harden the coating resin contained in the coating liquid on the surface of the carrier core 21. In this manner, the coating layer 22 is formed on the surface of the carrier core 21. The predetermined drying temperature is preferably 70°C or more and 80°C or less. The predetermined baking temperature is preferably 200°C or more and 300°C or less.
[0070] The coverage of the carrier cores 21 with the coating layer 22 can be adjusted, for example, by changing the predetermined drying temperature and the amount of coating liquid sprayed onto the carrier cores 21. The higher the predetermined drying temperature, the more the coating liquid dries before spreading over the entire surface of the carrier cores 21. For this reason, the higher the predetermined drying temperature, the more the coating layer 22 is formed on part of the surface of the carrier cores 21 rather than on the entire surface, and the lower the coverage tends to be. Also, the smaller the amount of coating liquid sprayed onto the carrier cores 21, the lower the coverage tends to be.
[0071] <Toner and carrier mixing process> In a mixing step of the toner and the carrier, the developer 1 is obtained by mixing the toner and the carrier using a mixer. EXAMPLES
[0072] The present invention will be described in more detail below using examples, but the present invention is not limited to the scope of the examples.
[0073] <Preparation of carrier coating liquid> First, coating liquids (L1) to (L20) were prepared. The compositions of the coating liquids (L1) to (L20) are shown in Tables 1 and 2. The coating liquids (L1) to (L20) are used to form a coating layer of the carrier.
[0074] [Table 1]
[0075] [Table 2]
[0076] The meanings of the terms in Tables 1 and 2 are as follows: wt%: mass%. Part: Part by mass. KR-255: Silicone resin solution ("KR-255" manufactured by Shin-Etsu Chemical Co., Ltd., solid content: methylphenyl silicone resin, solid content concentration: 50% by mass). KR-301: Silicone resin solution ("KR-301" manufactured by Shin-Etsu Chemical Co., Ltd., solid content: methylphenyl silicone resin, solid content concentration: 40% by mass). ES-1001N: silicone resin solution ("ES-1001N" manufactured by Shin-Etsu Chemical Co., Ltd., solid content: epoxy resin modified silicone resin, solid content concentration: 45% by mass). Solids concentration: The solids concentration of the silicone resin solution (unit: mass%). Amount of solution: Amount of silicone resin solution (unit: parts by mass). "Amount" in the "Coating Resin" column: the amount of coating resin. The amount of coating resin is the solid content of the coating resin. The amount of coating resin is calculated using the formula "[Amount of coating resin (unit: parts by mass)] = [Amount of silicone resin solution (unit: parts by mass)] x [Solid content concentration of silicone resin solution (unit: mass %)] / 100." For example, the amount of coating resin in the coating liquid (L1) is calculated to be 100.0 (= 200.0 x 50 / 100) parts by mass. BT: barium titanate. "Diameter" in the "BT" column: Number-average primary particle diameter of barium titanate particles (unit: nm). Z (BT / coating resin): BT / coating resin ratio. The BT / coating resin ratio is calculated from the formula "BT / coating resin ratio (unit: mass%) = 100 x [amount of barium titanate particles (unit: mass parts)] / [amount of coating resin (unit: mass parts)]". For example, the BT / coating resin ratio of the coating liquid (L1) is calculated to be 10.0 (= 100 x 10.0 / 100.0) mass%.
[0077] (Preparation of Coating Liquid (L1)) 200.0 parts by mass of silicone resin solution (KR-255, solid content: 100.0 parts by mass), 10.0 parts by mass of barium titanate (manufactured by Kyoritsu Materials Co., Ltd., number average primary particle diameter: 300 nm), and 3.0 parts by mass of carbon black ("Ketjen Black EC600JD" manufactured by Lion Specialty Chemicals Co., Ltd., conductive carbon black, DBP oil absorption: 495 cm 3 / 100g, BET specific surface area: 1270m 2 / g, number average primary particle diameter: 34.0 nm) and 800.0 parts by mass of toluene were mixed to obtain a coating liquid (L1).
[0078] (Preparation of Coating Solutions (L2) to (L6), (L11) to (L16), and (L19) to (L20)) Except for changing the amount of barium titanate from 10.0 parts by mass to the amount shown in Tables 1 and 2, each of the coating solutions (L2) to (L6), (L11) to (L16), and (L19) to (L20) was prepared in the same manner as the preparation of the coating solution (L1).
[0079] (Preparation of Coating Liquid (L7)) A coating liquid (L7) was prepared in the same manner as in the preparation of the coating liquid (L1), except that 200.0 parts by mass of the silicone resin solution (KR-255) was changed to 250.0 parts by mass of the silicone resin solution (KR-301), and the amount of toluene was changed from 800.0 parts by mass to 750.0 parts by mass.
[0080] (Preparation of Coating Liquid (L8)) A coating liquid (L8) was prepared in the same manner as in the preparation of the coating liquid (L1), except that 200.0 parts by mass of the silicone resin solution (KR-255) was changed to 222.2 parts by mass of the silicone resin solution (ES-1001N), and the amount of toluene was changed from 800.0 parts by mass to 777.8 parts by mass.
[0081] (Preparation of Coating Solutions (L9) to (L10) and (L17) to (L18)) Coating solutions (L9) to (L10) and (L17) to (L18) were prepared in the same manner as in the preparation of coating solution (L1), except that barium titanate having a number average primary particle diameter of 300 nm was replaced with barium titanate having a number average primary particle diameter shown in Tables 1 and 2. All of the barium titanates having number average primary particle diameters shown in Tables 1 and 2 were manufactured by Kyoritsu Material Co., Ltd.
[0082] <Synthesis of amorphous polyester resin (R1)> A non-crystalline polyester resin (R1) for use as a binder resin for toner base particles was synthesized by the following method. First, a reaction vessel equipped with a thermometer (thermocouple), a dehydration tube, a nitrogen introduction tube, and a stirring device (stirring blade) was set in an oil bath. 1575 g of BPA-PO (bisphenol A propylene oxide adduct), 163 g of BPA-EO (bisphenol A ethylene oxide adduct), 377 g of fumaric acid, and 4 g of catalyst (dibutyltin oxide) were put into this reaction vessel. Then, after the reaction vessel was filled with nitrogen, the temperature in the reaction vessel was raised to 220° C. using an oil bath while stirring the contents. Under the conditions of a nitrogen atmosphere and a temperature of 220° C., the contents of the reaction vessel were polymerized for 8 hours while distilling off by-product water. Then, the pressure in the reaction vessel was reduced, and the contents of the reaction solution were polymerized for another hour under the conditions of a reduced pressure atmosphere (pressure: 60 mmHg) and a temperature of 220° C. Subsequently, the temperature in the reaction vessel was lowered to 210°C, and then 336 g of trimellitic anhydride was added to the reaction vessel. The contents of the reaction vessel were reacted under conditions of a reduced pressure atmosphere (pressure: 60 mmHg) and a temperature of 210°C. The reaction time in the reaction was adjusted so that the physical properties of the reaction product, the amorphous polyester resin (R1), were as follows. The reaction product was then taken out of the reaction vessel and cooled to obtain an amorphous polyester resin (R1) having the following physical properties. The obtained polyester resin (R1) was determined to be amorphous because no clear endothermic peak was confirmed in the endothermic curve measured using a differential scanning calorimeter and no clear melting point could be measured.
[0083] (Physical properties of amorphous polyester resin (R1)) Softening point (Tm): 100℃ Glass transition temperature (Tg): 50℃ Mass average molecular weight (Mw): 30,000 Acid value: 15mgKOH / g Hydroxyl value: 30mgKOH / g
[0084] <Preparation of toner base particles> Using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.), 100 parts by mass of binder resin, 4 parts by mass of colorant, 1 part by mass of charge control agent, and 5 parts by mass of release agent were mixed to obtain a mixture. The amorphous polyester resin (R1) obtained in the above <Synthesis of amorphous polyester resin (R1)> was used as the binder resin. The copper phthalocyanine blue pigment (CI Pigment Blue 15:3) was used as the colorant. The quaternary ammonium salt ("BONTRON (registered trademark) P-51" manufactured by Orient Chemical Industry Co., Ltd.) was used as the charge control agent. The carnauba wax ("Special Carnauba Wax No. 1" manufactured by Kato Yoko Co., Ltd.) was used as the release agent. The obtained mixture was melt-kneaded using a twin-screw extruder ("PCM-30" manufactured by Ikegai Co., Ltd.) to obtain a melt-kneaded product. The melt-kneaded product was pulverized using a mechanical pulverizer (Turbo Mill, manufactured by Freund Turbo Corporation) to obtain a pulverized product. The pulverized product was classified using a classifier (Elbow Jet, manufactured by Nittetsu Mining Co., Ltd.). As a result, powdered toner base particles with a volume median diameter of 6.8 μm were obtained.
[0085] <Toner Preparation> Toners for developers (A-1) to (A-19) and (B-1) to (B-12) were prepared. The compositions of these toners are shown in Tables 3 and 4 below. For the sake of simplicity, even when a toner having the same composition as the toner for developer (A-1) is used, it is shown in Tables 3 and 4 as a toner for a developer with a different developer number.
[0086] (Preparation of toner for developer (A-1)) 100.00 parts by mass of the toner base particles obtained in the above <Preparation of toner base particles>, 1.50 parts by mass of silica particles, and 0.50 parts by mass of strontium titanate particles (number average primary particle diameter: 80 nm) were mixed for 5 minutes at 4,000 rpm using an FM mixer ("FM-10B" manufactured by Nippon Coke & Engineering Co., Ltd.). As the silica particles, "AEROSIL (registered trademark) REA90" (dry silica particles with positive charging property imparted by surface treatment, number average primary particle diameter 20 nm) manufactured by Nippon Aerosil Co., Ltd. was used. As the strontium titanate particles, "SW-100" (number average primary particle diameter: 80 nm, undoped strontium titanate) manufactured by Titan Kogyo Co., Ltd. was used. The resulting mixture was sieved using a 200 mesh (75 μm opening) sieve to obtain a toner for developer (A-1).
[0087] (Preparation of toners for developers (A-2) to (A-19) and (B-1) to (B-12)) Each of the toners for developers (A-2) to (A-19) and (B-1) to (B-12) was prepared by the same method as for preparing the toner for developer (A-1), except that strontium titanate particles having a number-average primary particle diameter shown in Tables 3 and 4 were used in the amounts shown in Tables 3 and 4. For example, in preparing the toner for developer (A-2), 0.85 parts by mass of strontium titanate particles having a number-average primary particle diameter of 80 nm was used, as shown in the "Developer (A-2)" column.
[0088] In preparing the toner for developer (A-8), strontium titanate particles (number average primary particle diameter: 50 nm, undoped strontium titanate) manufactured by Titan Kogyo Co., Ltd. were used as the strontium titanate particles. In preparing the toner for developer (A-9), strontium titanate particles (number average primary particle diameter: 20 nm, undoped strontium titanate) manufactured by Titan Kogyo Co., Ltd. were used as the strontium titanate particles.
[0089] <Preparation of Carrier> Carriers for developers (A-1) to (A-19) and (B-1) to (B-12) were prepared. The compositions of these carriers are shown in Tables 3 and 4 described below. For the sake of simplicity, even when a carrier having the same composition as the carrier for developer (A-1) is used, it is shown in Tables 3 and 4 as a carrier for a developer with a different developer number. In addition, to facilitate understanding, the number average primary particle diameter and Z value of the barium titanate particles shown in Tables 1 and 2 are also shown in Tables 3 and 4.
[0090] (Preparation of Carrier for Developer (A-1)) Using a fluidized bed coating device (Powrex Corporation, "FD-MP-01 D type"), 1000 g of carrier cores were fluidized while spraying the coating liquid (L1) onto the carrier cores. In this way, carrier cores coated with the coating liquid (L1) were obtained. The coating conditions were an inlet air temperature of 75°C, an inlet air volume of 0.3 m3, and a 1000 g / m2 nozzle. 3 The conditions were: 1. rpm, and the rotor rotation speed was 400 rpm. Manganese ferrite core (manufactured by DOWA IP Creation Co., Ltd., volume median diameter: 34.7 μm, saturation magnetization: 80 emu / g) was used as the carrier core. The amount of coating liquid (L1) put into the fluidized bed coating device was adjusted so that the coating layer / core ratio was 2.2 mass% (i.e., the mass of the coating layer was 22 g for 1000 g of carrier core). Specifically, 197.22 g of coating liquid (L1) was used. 197.22g of the coating liquid (L1) contained 38.94g of silicone resin solution (KR-255) (solid content: 19.47g), 1.95g of barium titanate (solid content: 1.95g), 0.58g of carbon black (solid content: 0.58g), and 155.75g of toluene, and the total solid content of 197.22g of the coating liquid (L1) was 22.00g (=19.47+1.95+0.58). Next, the carrier core coated with the coating liquid (L1) was heated at 250°C for 2 hours using an oven. In this way, a coating layer was formed on the surface of the carrier core to obtain a carrier for developer (A-1).
[0091] (Preparation of Carriers for Developers (A-2) to (A-19) and (B-1) to (B-12)) Each of the carriers for developers (A-2) to (A-19) and (B-1) to (B-12) was prepared in the same manner as in the preparation of the carrier for developer (A-1), except that barium titanate having the volume median diameter and saturation magnetization shown in Tables 3 and 4 was used, that the coating liquid shown in Tables 3 and 4 was used, and that the amount of the coating liquid charged into the fluidized bed coating apparatus was adjusted so as to obtain the coating layer / core ratio shown in Tables 3 and 4.
[0092] For example, in the preparation of the carrier for developer (A-2), coating liquid (L2) was used as shown in the "Developer (A-2)" column. In addition, in the preparation of the carrier for developer (A-2), the amount of coating liquid (L2) put into the fluidized bed coating device was adjusted so that the coating layer / core ratio was 2.2 mass% (i.e., the mass of the coating layer was 22 g for 1000 g of carrier core). Specifically, 186.97 g of coating liquid (L2) was used. The 186.97 g coating liquid (L2) contained 36.66 g of silicone resin solution (KR-255) (solid content: 18.33 g), 3.12 g of barium titanate (solid content: 3.12 g), 0.55 g of carbon black (solid content: 0.55 g), and 146.64 g of toluene, and the total amount of solids contained in the 186.97 g coating liquid (L2) was 22.00 g (= 18.33 + 3.12 + 0.55).
[0093] In addition, in preparing the carrier for developer (A-10), a manganese ferrite core (manufactured by DOWA IP Creation Co., Ltd., volume median diameter: 20.3 μm, saturation magnetization: 67 emu / g) was used as the carrier core. In preparing the carrier for developer (A-11), a manganese ferrite core (manufactured by DOWA IP Creation Co., Ltd., volume median diameter: 58.8 μm, saturation magnetization: 87 emu / g) was used as the carrier core.
[0094] <Methods for measuring saturation magnetization, volume median diameter, and number average primary particle diameter> The saturation magnetization of the carrier core was measured using a high-sensitivity vibrating sample magnetometer ("VSM-P7" manufactured by Toei Kogyo Co., Ltd.) under the condition of an external magnetic field of 3000 (unit: Oe).
[0095] The volume median diameter (ie, median diameter) of the carrier core was measured using a laser diffraction / scattering type particle size distribution measuring device ("LA-950" manufactured by Horiba, Ltd.).
[0096] The number-average primary particle diameter of the strontium titanate particles and barium titanate particles was measured using a scanning electron microscope (field emission scanning electron microscope, "JSM-7600F" manufactured by JEOL Ltd.) In measuring the number-average primary particle diameter, the circle-equivalent diameter (Heywood diameter: diameter of a circle having the same area as the projected area of the primary particle) of 100 primary particles was measured, and the number average value was calculated.
[0097] <Evaluation of fogging suppression> First, a developer to be used for evaluating fogging suppression was prepared. Specifically, 9 parts by mass of toner and 100 parts by mass of carrier were mixed for 30 minutes using a shaker mixer (Turbler (registered trademark) Mixer T2F manufactured by Willy & Bachofen (WAB)) to obtain a developer with a toner concentration of 9% by mass. The toner and carrier shown in Tables 3 and 4 were used to prepare the developer. For example, the toner for developer (A-1) and the carrier for developer (A-1) shown in the "Developer (A-1)" column in Table 3 were used to prepare developer (A-1).
[0098] Next, the evaluation of fogging suppression was performed in a normal temperature and humidity environment (temperature 25°C and relative humidity 50%RH). A developer with a toner concentration of 9% by mass was put into the cyan developing device of the evaluation machine ("TASKalfa 5052ci" manufactured by Kyocera Document Solutions Inc.), and a refill toner was put into the cyan toner container. Image I (image with a print rate of 2%) was continuously printed on 10,000 sheets of A4 size paper using the evaluation machine. Immediately after that, image II (image with a print rate of 20%) was continuously printed on 100 sheets of A4 size paper using the evaluation machine. The reflection density of the blank area of the paper on which image II was printed on the 100th sheet was measured using a white light meter ("TC-6DS" manufactured by Tokyo Denshoku Co., Ltd.). Then, the fogging density was calculated based on the formula "fogging density = reflection density of blank area - reflection density of unprinted paper". The evaluation of fogging suppression was judged according to the following criteria. The measured fog densities and the evaluation results are shown in Tables 5 and 6.
[0099] (Evaluation Criteria for Fog Suppression) A (good): The fog density is less than 0.010. B (bad): The fog density is 0.010 or more.
[0100] <Evaluation of charging stability against changes in toner concentration in developer> The evaluation of the charge stability against the change in toner concentration in the developer was carried out in a normal temperature and humidity environment (temperature 25°C and relative humidity 50%RH). 10.0 g of carrier and 0.3 g of toner were placed in a 20 mL poly bottle. The contents of the poly bottle were stirred for 30 minutes at a rotation speed of 96 rpm using a shaker mixer (Turbler (registered trademark) Mixer T2F manufactured by Willy & Bachofen (WAB)). Immediately after stirring, the charge amount (unit: μC / g) of the toner contained in the developer in the poly bottle was measured using a suction type small charge amount measuring device (Model 212HS manufactured by Trek). The measured charge amount was taken as the charge amount of the toner when the toner concentration in the developer was 3% by mass (hereinafter referred to as "T / C3% charge amount").
[0101] The charge amount of the toner when the toner concentration in the developer is 6% by mass (hereinafter referred to as "T / C6% charge amount") was measured by the same method as that for measuring the T / C3% charge amount, except that 10.0 g of carrier and 0.6 g of toner were placed in the poly bottle. The charge amount of the toner when the toner concentration in the developer is 9% by mass (hereinafter referred to as "T / C9% charge amount") was measured by the same method as that for measuring the T / C3% charge amount, except that 10.0 g of carrier and 0.9 g of toner were placed in the poly bottle. From these measured charge amounts, the slope was calculated according to the formula "(slope)={[(T / C3% charge amount)-(T / C9% charge amount)]÷6}÷(T / C6% charge amount)". Note that the slope (the amount of change in the charge amount of the toner relative to the change in the toner concentration in the developer) is affected by the absolute value of the charge amount, so the above formula is corrected by dividing by the T / C6% charge amount. The smaller the slope, the smaller the fluctuation in the charge amount of the toner is even when the toner concentration in the developer changes. The evaluation of the charge stability against the change in the toner concentration in the developer was judged according to the following criteria. The calculated slope and the judgment results are shown in Tables 5 and 6.
[0102] (Evaluation standard for charge stability against changes in toner concentration in developer) A (Good): The slope is less than 0.090. B (bad): The slope is 0.090 or more.
[0103] The meanings of the terms in Tables 3 and 4 are as follows. wt%: mass%. Part: Part by mass. Base particles: toner base particles. ST: Strontium titanate. "Diameter" in the "ST" column: Number-average primary particle diameter of strontium titanate particles (unit: nm). BT: barium titanate. "Diameter" in the "BT" column: Number-average primary particle diameter of barium titanate particles (unit: nm). Core: Career Core. "Diameter" in the "Core" column: Volume median diameter of the carrier core (unit: μm). X(ST / parent particle): ST / parent particle ratio. The ST / parent particle ratio is calculated from the formula "ST / parent particle ratio (unit: mass %) = 100 x [amount of strontium titanate particles (unit: mass parts)] / [amount of toner parent particles (unit: mass parts)]". For example, the ST / parent particle ratio of the toner for developer (A-1) is calculated to be 0.50 (= 100 x 0.50 / 100.0) mass %. X×10: ST / parent particle ratio multiplied by 10. Coat layer / core: Coat layer / core ratio. The coat layer / core ratio is calculated from the formula "[Coat layer / core ratio (unit: mass%)] = 100 × [mass of coat layer (unit: mass parts)] / [mass of carrier core (unit: mass parts)] = 100 × [mass of solid content of coating liquid (unit: mass parts)] / [mass of carrier core (unit: mass parts)] = 100 × {[solid content of silicone resin solution (unit: mass parts)] + [mass of barium titanate (unit: mass parts)] + [mass of carbon black (unit: mass parts)]} / [mass of carrier core (unit: mass parts)]". For example, the calculation method of the coat layer / core ratio of the carrier for developer (A-1) is as described above (Preparation of carrier for developer (A-1)). Z (BT / coating resin): This has the same meaning as Z (BT / coating resin) in Tables 1 and 2.
[0104] The meanings of the terms in Tables 5 and 6 are as follows. FD: Fog density. Charge amount (T / C=3%): T / C3% charge amount (unit: μC / g). Charge amount (T / C=6%): T / C6% charge amount (unit: μC / g). Charge amount (T / C=9%): T / C9% charge amount (unit: μC / g).
[0105] [Table 3]
[0106] [Table 4]
[0107] [Table 5]
[0108] [Table 6]
[0109] As shown in Table 4, for developer (B-1), the ST / parent particle ratio was more than 0.90% by mass. For developer (B-2), the ST / parent particle ratio was less than 0.30% by mass. For developers (B-4), (B-6), and (B-12), Z≦45.0 in formula (1) was not satisfied. For developer (B-8), the number average primary particle diameter of the barium titanate particles was more than 500 nm. For developer (B-9), the coat layer / core ratio was less than 2.0% by mass. For this reason, as shown in Table 6, the evaluation of fogging suppression for developers (B-1), (B-2), (B-4), (B-6), (B-8), (B-9), and (B-12) was poor.
[0110] As shown in Table 4, developers (B-3), (B-5), and (B-11) did not satisfy (X×10)≦Z in formula (1). For developer (B-7), the number-average primary particle diameter of barium titanate particles was less than 100 nm. Therefore, as shown in Table 6, the evaluation of the charging stability against the change in toner concentration in developers (B-3), (B-5), (B-7), and (B-11) was poor.
[0111] As shown in Table 4, the coat layer / core ratio of developer (B-10) exceeded 4.0% by mass. Therefore, as shown in Table 6, the evaluation of developer (B-10) for fogging suppression and the evaluation of charging stability against toner concentration change in the developer were both poor.
[0112] As shown in Tables 3 and 4, the developers (A-1) to (A-19) had the following configurations. That is, the ST / parent particle ratio was 0.30% by mass or more and 0.90% by mass or less. The coating layer of the carrier particles contained a coating resin and barium titanate particles, and the coating resin contained a silicone resin. The number average primary particle diameter of the barium titanate particles was 100 nm or more and 500 nm or less. The coating layer / core ratio was 2.0% by mass or more and 4.0% by mass or less. The BT / coating resin ratio satisfied formula (1). Therefore, as shown in Tables 5 and 6, the evaluation of the fogging suppression of the developers (A-1) to (A-19) and the evaluation of the charging stability against the change in toner concentration in the developers were both good.
[0113] From the above, it was shown that the developers of the present invention, including developers (A-1) to (A-19), can form images with less fog, and that even when the toner concentration in the developer changes, the fluctuation in the toner charge amount is small. [Industrial Applicability]
[0114] The developer according to the present invention can be used to form an image in, for example, a copier, a printer, or a multifunction machine.
Claims
1. A toner including toner particles and a carrier including carrier particles, The toner particles include toner base particles and external additive particles provided on the surfaces of the toner base particles, The external additive particles include strontium titanate particles, a first content rate, which is a content rate of the strontium titanate particles relative to the mass of the toner base particles, is 0.30% by mass or more and 0.90% by mass or less; The carrier particles have a carrier core and a coating layer that covers the surface of the carrier core, The coating layer contains a coating resin and barium titanate particles, The coating resin includes a silicone resin, The number average primary particle diameter of the barium titanate particles is 100 nm or more and 500 nm or less, a second content ratio, which is a content ratio of the coating layer to the mass of the carrier core, is 2.0 mass% or more and 4.0 mass% or less; A two-component developer, wherein a third content rate, which is a content rate of the barium titanate particles relative to the mass of the coating resin, satisfies formula (1). (X × 10) ≦ Z ≦ 45.0 ... (1) (In the formula (1), X represents the first content, and Z represents the third content.)
2. 2. The two-component developer according to claim 1, wherein the carrier core has a volume median diameter of 20.0 μm or more and 60.0 μm or less.
3. The two-component developer according to claim 1 , wherein the coating layer further contains carbon black particles.
4. 2. The two-component developer according to claim 1, wherein the strontium titanate particles of the toner particles have a number average primary particle diameter of 20 nm or more and 80 nm or less.
5. 2. The two-component developer of claim 1, wherein the strontium titanate particles of the toner particles are undoped strontium titanate particles.
Citation Information
Patent Citations
Carrier for developer, developer and image forming method
JP2003280284A
Carrier and two-component developer
JP2007033631A
Electrostatic charge image developer, developer cartridge, process cartridge, image forming apparatus, and image forming method
JP2018142017A
Two-component developer
JP2020034599A
Electrostatic image developer, process cartridge, image forming device, and image forming method
JP2020154225A